2021
DOI: 10.3892/etm.2021.10119
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface complications result from dysregulation of the OGF‑OGFr signaling pathway in female diabetic rats

Abstract: Approximately 4.5 million women in the United States exhibit diabetes-associated ocular complications. The time course and magnitude of these complications, and their association with the dysregulation of the opioid growth factor (OGF)-OGF receptor (OGFr) signaling pathway are unknown. The present study investigated the onset and magnitude of ocular surface complications and the association with a dysregulated OGF-OGFr signaling pathway in diabetic female rats. Adult female Sprague-Dawley rats were injected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…The onset and magnitude of diabetes complications are associated with the elevations of OGF tissue and serum levels in diabetic rats [ 36 , 38 , 39 , 40 ]. These complications appear with more frequency and severity in female animal models, similarly associated with descended estradiol levels and elevated OGF levels [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The onset and magnitude of diabetes complications are associated with the elevations of OGF tissue and serum levels in diabetic rats [ 36 , 38 , 39 , 40 ]. These complications appear with more frequency and severity in female animal models, similarly associated with descended estradiol levels and elevated OGF levels [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research has shifted to focus on the timing of the onset of corneal complications in T1D rats, with follow up studies exploring whether prophylactic administration of NTX beginning at the appearance of hyperglycemia can prevent or delay the onset of dry eye, deceased corneal sensitivity, and delayed corneal epithelial wound healing [ 14 , 15 ]. Given the relative prevalence of disease in both genders, studies on female rats were indicated [ 16 ]. The time course and magnitude of ocular surface complications and their association with the dysregulation of the OGF - OGFr signaling pathway were determined in a cohort of male and female T1D rats some of which received insulin implants in order to maintain blood glucose levels.…”
Section: Elevated Ogf Levels As a Biomarkermentioning
confidence: 99%
“…The highest T1D male OGF level was approximately 60 pg/ml. Increases in enkephalin levels in diabetes have been documented in humans [ 22 ] and mice [ 23 ], but the sex differences related to the timing of the rapid increase within a few weeks of hyperglycemia is novel [ 14 , 16 ]. These differences may explain in part the early on set of complications in female rats.…”
Section: Correlation Of Ocular Surface Complications Ogf Blood Levels...mentioning
confidence: 99%
See 2 more Smart Citations